Medication-related harm: a geriatric syndrome. (28th October 2019) - Stevenson, Jennifer M; Davies, J Graham; Martin, Finbarr C
Abstract: The WHO Global Patient Safety Challenge: Medication Without Harm recognises medication-related harm (MRH) as a global public health issue. Increased life-expectancy coupled with multimorbidity and polypharmacy leads to an increased incidence of MRH, especially in older adults: at a cost of approximately £400 million to the National Health Service (NHS) in England. Harm from medicines has long been recognised by geriatricians, and strategies have been developed to mitigate harm. In general, these have focused on the challenges of polypharmacy and appropriateness of medicines, but impact on the quality of life, clinical and economic outcomes has been variable and often disappointing. The problem of MRH in older adults will continue to grow unless a new approach is adopted. Emerging evidence suggests that we need to take a broader approach as described in our conceptual model, where well-recognised physiological changes are incorporated, as well as other rarely considered psychosocial issues that influences MRH. Parallels may be drawn between this approach and the management of geriatric syndromes. We propose there must be a greater emphasis on MRH, and it, of itself, should be considered as a geriatric syndrome, to bring the spotlight onto the problem and to send a clear signal from geriatric experts that this is an important issue that needs to be addressed using a co-ordinated and tailored approach across health and social care boundaries. This requires a more proactive approach to monitor and review the medicines of older adults in response to their changing need.